Family medicine: Conceptualization, experiences and pedagogical practice in community training - Triana-Ramírez, Alba Nidia; Universidad Pedagógica y Tecnológica de Colombia; Vargas- Torres, Ludy Alexandra; Universidad Pedagógica y Tecnológica de Colombia; Salamanca Velandia, Claudia Tatiana; Universidad Pedagógica y Tecnológica de Colombia; Ascanio Noreña, Catalina; Badoui Rodríguez, Nora; Pérez Becerra, Francy Nelly; Universidad Pedagógica y Tecnológica de Colombia; Giraldo González, Ximena; Peña Torres, Olga Lucía (UPTC Editorial, 2023)
Family Medicine is a medical specialty that provides continuous and integral attention to the individual, the family and the  communities, covers all ages, genders and clinical problems. Also, take Primary Health Care as a basis for their professional practice (APS) and integrates the biological, clinical and behavioral sciences, from the biopsychosocial model, the approach of social determinants health and sustainable development goals. This book shows some conceptual dynamics, based on experiences and pedagogical practices for the community formation of the specialist in Family Medicine with the aim of  providing epistemological foundations and methodologies for the community approach. starting scenarios in the territories  (urban and rural), social and institutional, promotes individual comprehensive care in the training component, family and particularly community and provision of the service of humanized health.